2021
DOI: 10.5114/ms.2021.109530
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and flutter – the state of the art. Part 2

Abstract: Despite constantly updating our knowledge on atrial fibrillation and flutter there are many questions and doubts about the nature and extent of arrhythmic and non-arrhythmic consequences of these arrhythmias. In part 1 of the state-of-the-art paper the diagnostic work-up of patients with the 2 arrhythmias was summarized. The management of patients with atrial fibrillation and flutter requires a multidisciplinary approach in the risk assessment (including stroke) and treatment strategy. Regardless of the type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 88 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Stroke risk stratification in patients with AFL remains a complicated issue [1,[9][10][11][12]. Left atrial appendage thrombus (LAAT) is regarded as a risk factor for stroke in these patients; however, the actual LAATrelated health risk in patients with AFL on chronic anticoagulation remains unknown [13]. Moreover, the risk factors and prevalence of LAAT in patients with AFL on oral anticoagulation (OAC) (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stroke risk stratification in patients with AFL remains a complicated issue [1,[9][10][11][12]. Left atrial appendage thrombus (LAAT) is regarded as a risk factor for stroke in these patients; however, the actual LAATrelated health risk in patients with AFL on chronic anticoagulation remains unknown [13]. Moreover, the risk factors and prevalence of LAAT in patients with AFL on oral anticoagulation (OAC) (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the risk factors and prevalence of LAAT in patients with AFL on oral anticoagulation (OAC) (i.e. non-VKA oral anticoagulants (NOACs) and vitamin K antagonists (VKAs)) have not been fully established [13]. It seems that the actual LAAT-related health risk varies according to thrombus age, medical management, and procedures (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention of stroke and thromboembolic events remains an essential part of AF treatment according to the recommendations of the European Society of Cardiology and the American Heart Association; however, improved symptom management and optimal cardiovascular and comorbidity management are equally important [2,3]. There are 2 therapeutic strategies for AF: rhythm and heart rate control strategies [2,3], but the evidence on the comparable health effects of these strategies is unclear [4]. Previous trials, such as AFFIRM, RACE, STAF, PIAF, and HOT CAFE, have not shown the superiority of rhythm control over rate control in improving cardiovascular outcomes and reducing mortality in patients with AF; however, many post-hoc analyses have disclosed the advantages of sinus rhythm (SR) maintenance, including improved physical capacity [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%